New Paradigm Using Chaos Theory to Understand the Evolution of Pandemics in Mexican Society: An Essay Applied to COVID-19 - Lagunas Puls, Sergio (2025)
The hypothesis of this work, in line with the fundamental premise of chaos theory, is that the initial conditions of a pandemic—specifically hospital incidence, influenced by the growth rate—affect the predictability of its evolution. As the relative population of infected individuals grows and combines with higher growth rates, subsequent expectations over time would cease to follow logistic projections, resulting in chaotic conditions. This research aims to present rigorous scenarios for evaluating the COVID- 19 pandemic in Mexico to demonstrate why it is necessary to study pandemics as chaotic systems. The approach and results can strengthen public policies, enabling authorities to anticipate the onset of chaotic conditions in Mexico’s eight regions.